[BP.12.02] PLASMA POTASSIUM NEGATIVELY EFFECTS ABUNDANCE OF THE THAIZIDE SENSITIVE SODIUM-CHLORIDE COTRANSPORTER IN HUMANS. (September 2017) - Wolley, M.; Wu, A.; Gordon, R.D.; Fenton, R.; Stowasser, M.
Abstract : Objective: The thiazide sensitive sodium-chloride cotransporter (NCC) is important for sodium reabsorption and blood pressure. With-no-lysine-kinase 4 (WNK4) is now thought to be an important regulator of NCC, and is mutated in some cases of Gordon's syndrome, causing hypertension and hyperkalaemia. We have previously demonstrated that WNK4 and NCC in human urinary exosomes appears to be sensitive to mineralocorticoids, but recent animal studies suggest that potassium is a dominant regulator of NCC, possibly via regulation of WNK4. The aim of this study was to determine associations between plasma potassium, NCC and associated proteins in patients during workup for primary aldosteronism. Design and method: We isolated urinary exosomes from 26 subjects (20 with primary aldosteronism and 6 cured after adrenalectomy for aldosterone producing adenoma), before fludrocortisone suppression testing and again after 3 days of fludrocortisone administration, and quantified abundance of NCC, phosphorylated NCC (pNCC) and WNK4 by western blot. Results: The patients with cured primary aldosteronism had lower aldosterone (144 pmol/L vs 643, p < 0.001 and a higher potassium (4.7 mmol/L vs 3.6, p < 0.001) compared to those with primary aldosteronism. NCC was >4 fold, pNCC was >5.5 fold, and WNK4 was >6 fold higher in patients with primary aldosteronism compared to those who had been cured (p < 0.05 for all). There were very strong negative correlations at baseline between plasma potassium and WNK4 (R2 = 0.57, p < 0.001), NCC (R2 = 0.66, p < 0.001) and pNCC (R2 = 0.43, p < 0.01). There were weaker positive associations between plasma aldosterone and NCC (R2 = 0.34, p < 0.01) and WNK4 R2 = 0.24, p = 0.03). After 3 days of fludrocortisone administration however there was no apparent relationship between potassium and abundance of NCC, WNK4 or pNCC. Conclusions: NCC and its phosphorylated form pNCC are upregulated in primary aldosteronism, along with the regulatory kinase WNK4. Plasma potassium is closely related to the abundance of WNK4, NCC and pNCC, suggesting it potassium plays a role in NCC regulation, but might be over-ridden by mineralocorticoid stimulation in some circumstances.